RESEARCH ON THE SOCIAL INFRASTRUCTURE: BIBLIOMETRIC ANALYSIS FROM 1990 – 2024 - Fatur Rohman, Ahmad Nizar; Widianingsih, Ida (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2024)
Bibliometric studies have been utilized as analysis tools to explore publications and scientific research on the topic, from the novelty of scientific maps to the scheme of the bibliometric. Meanwhile, the systematic procedural explained in the series of bibliometrics, on the other hand, needs to be conducted by the researchers. However, the concise research procedure on bibliometric analysis is a valuable tool to project research gaps, tentative trends, co-occurrence, and authorship. The topic chosen is social infrastructure, which needs to be identified for bibliometric analysis. Consequently, the paper aims to conduct a comprehensive bibliometric of social infrastructure. Collected data from Scopus include 4,111 publications retrieved from the database. Moreover, bibliometrics has a couple of significant analyses of the domain (level of analysis) and knowledge structure. The results indicated a remarkable footprint for social infrastructure research involving authors, sources, and publications following this subject. Likewise, the nation and association produced significant efforts towards the subject. Consecutively, the science mapping approach was thoroughly confiscated, including social infrastructure-related research, intellectual research, and the structure of the topic. In-depth overviews and notions connected to social infrastructure are valid sources for study and practice.Keywords: Bibliometric Analysis, Domain, Scientific Structure, Social Infrastructure.